Factors Affecting Nursing Students Learning in Clinical from Student Viewpoint at Taif University - Suheir. A.M. Sayed, Alsuwat, Sarab, Alsufyani, Jamilah, Althobyani, Amjad, Alharthi, Maha, Almutairi ,Samiyah, Alqurqshi, Amani, Almwllad,Noha (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Clinical practice is important because it allows students to apply their theoretical knowledge in a real environment, develop psychomotor skills, observe and adapt the professional role. In clinical practice, many factors may affect students’ learning. These factors are listed as These factors are listed as students related issues, clinical instructor related issues and clinical environment related issues. In order to plan an effective learning, it is essential to specify these factors and organize them in a way that will support the students’ learning. This research will discuss these factors in detail. Aim: The research aims was assessing the factors affecting nursing student learning in clinical practice Method: Descriptive cross-sectional community-based study was conducted at the University of Taif in the Kingdom of Saudi Arabia. The duration of the study spanned from August 2021- June 2022, the questionnaire was sent to participants via electronic links on Mobile phones, Results: the study consists of 218 participants, most of them from the fourth year , numbered 92, third year was 54, then the second year was number 41 and finally the first was 31 and most of them are females (62.8%) , 151 student did not have diseases (69.1% ) While 49 students had vision impairment (23.3%), Majority of the nursing students 128(58.7%) choosing nursing as a opportunity , the Majority 169 nursing Student agreed that worried about making mistakes in clinical placement while 96 students was said the characteristics of instructor is difficult and 86 students complain the instructor is more interested in their appearance more than their education , half the students 112 student They said there is a difference between theory and practical training and 73 students they said they needed more time for hospital training , the was statistic significant association between student related factors and A grade point average (p.v =.084) and also the was significant statistic association between Clinical related factors and A grade point average (p.v =.091) Conclusions: It is clear that all themes mentioned by the students play an important role in student learning and nursing education in general. Learning of students in clinical placements is affected by factors originating from themselves, the instructor and clinical wards. Readiness of students, personal and professional characteristics of instructor and attitudes of staff towards students in placements have importance on learning of students. Recommendation: Practical training is very important in the educational process. We recommend increasing the hours of practical training, link practice with the theoretical part and use modern methods in training Keywords: Clinical practice, Nursing Students, Learning, Student Viewpoint and Taif University